Poly-γ-Glutamic Acids Contribute to Biofilm Formation and Plant Root Colonization in Selected Environmental Isolates of Bacillus subtilis - Yu, Yiyang; Yan, Fang; Chen, Yun; Jin, Christopher; Guo, Jian-Hua; Chai, Yunrong (Frontiers in Microbiology, 2016)
Bacillus subtilis is long known to produce poly-γ-glutamic acids (γ-PGA) as one of the major secreted polymeric substances. In B. subtilis, the regulation of γ-PGA production and its physiological role are still unclear. B. subtilis is also capable of forming structurally complex multicellular communities, or biofilms, in which an extracellular matrix consisting of secreted proteins and polysaccharides holds individual cells together. Biofilms were shown to facilitate B. subtilis-plant interactions. In this study, we show that different environmental isolates of B. subtilis, all capable of forming biofilms, vary significantly in γ-PGA production. This is possibly due to differential regulation of γ-PGA biosynthesis genes. In many of those environmental isolates, γ-PGA seems to contribute to robustness and complex morphology of the colony biofilms, suggesting a role of γ-PGA in biofilm formation. Our evidence further shows that in selected B. subtilis strains, γ-PGA also plays a role in root colonization by the bacteria, pinpointing a possible function of γ-PGA in B. subtilis-plant interactions. Finally, we found that several pathways co-regulate both γ-PGA biosynthesis genes and genes for the biofilm matrix in B. subtilis, but in an opposing fashion. We discussed potential biological significance of that.